Effects of e-beam irradiation on amino acids, fatty acids, and volatiles of smoked duck meat during storage. (June 2018) - Jo, Yunhee; An, Kyung-A; Arshad, Muhammad Sajid; Kwon, Joong-Ho
Abstract: The effects of e-beam irradiation on changes in amino acids, fatty acids, and volatiles in smoked duck meat were investigated during refrigerated storage (0, 20, and 40 days) at 4 °C. Irradiation at 1.5 to 4.5 kGy led to significant variation in hydrolyzed amino acids (HAA), free amino acids (FAA), fatty acids, and volatile profiles. HAA contents did not show significant difference with respect to the applied irradiation dose, however FAA level significantly decreased according to a dose-dependent manner and storage time. Fatty acids showed a dose-dependent decrease but there was little effect of storage periods during 40 days. Trans-fatty acids were not observed in irradiated and non-irradiated smoked duck meat. The levels of acids and sulfur compounds decreased with increasing irradiation doses and storage periods, whereas alcohols, aldehydes, and phenols increased as the storage periods increased. Thus, optimum dose of irradiation < 3 kGy may not cause the quality changes in smoked duck meat during storage. Industrial relevance: Effects of e-beam irradiation were investigated on amino acids, fatty acids, and volatile profiles in smoked duck meat. E-beam irradiation applied at different doses may affect the contents of both hydrolyzed as well as free amino acids of smoked duck meat. The current research findings present the potential implications regarding effects of e-beam irradiation treatment on smoked duck meat during storage. Highlights: E-beam irradiation effects on smoked duck meat were evaluated. HAA contents did not show variations in dose dependent manner. FAA level significantly decreased with respect to dose and storage time. Trans-fatty acids were not observed in irradiated and non-irradiated samples. < 3 kGy dose did not cause quality changes in smoked duck meat during storage.